Sensing, Uptake and Catabolism of L-Phenylalanine During 2-Phenylethanol Biosynthesis via the Ehrlich Pathway in Saccharomyces cerevisiae - Dai, Jun; Xia, Huili; Yang, Chunlei; Chen, Xiong (Frontiers in Microbiology, 2021)
2-Phenylethanol (2-PE) is an important flavouring ingredient with a persistent rose-like odour, and it has been widely utilized in food, perfume, beverages and medicine. Due to the potential existence of toxic byproducts in 2-PE resulting from chemical synthesis, the demand for “natural” 2-PE through biotransformation is increasing. L-Phenylalanine (L-Phe) is used as the precursor for the biosynthesis of 2-PE through the Ehrlich pathway by Saccharomyces cerevisiae. The regulation of L-Phe metabolism in Saccharomyces cerevisiae is complicated and elaborate. We reviewed current progress on the signal transduction pathways of L-Phe sensing, uptake of extracellular L-Phe and 2-PE synthesis from L-Phe through the Ehrlich pathway. Moreover, the anticipated bottlenecks and future research directions for Saccharomyces cerevisiae biosynthesis of 2-PE are discussed.